Impact of Work From Home (WFH) on the Work-Life Balance of Professionals Working in the Telecommunications and Fast-Moving Consumer Goods (FMCG) Sector: An Exploratory Study in Bangladesh (Global Journal of Management and Business Research, 2022)
Purpose: This study explores the impact of work from home on the work-life balance of professionals mainly in two sectors and also finds out the preference for work modality Design/methodology/approach: We adopted a qualitative research design using a multiple case study method collecting data from six respondents working in different companies in Bangladesh.
Keywords: work from home; work-life balance; impacts; telecommunications; fast-moving consumer goods